Experimental Study on the Effect of Allogeneic Endothelial Progenitor Cells on Wound Healing in Diabetic Mice - Min Leng; Ying Peng; Manchang Pan; Hong Wang (Journal of Diabetes Research)
Endothelial progenitor cells (EPCs) are involved in the neovascularization in traumatic and ischemic sites, but EPCs are “detained” in bone marrow under diabetic conditions, which results in reduction of the number of EPCs and their biological activity in peripheral blood. Based on our previous study to mobilize autologous bone marrow EPCs by administering AMD3100+G-CSF to realize the optimal effect, our present study is aimed at exploring the effects of transplanting EPCs locally in a wound model of diabetic mice. First, we prepared and identified EPCs, and the biological functions and molecular characteristics were compared between EPCs from DB/+ and DB/DB mice. Then, we performed full-thickness skin resection in DB/DB mice and tested the effect of local transplantation of EPCs on skin wound healing. The wound healing process was recorded using digital photographs. The animals were sacrificed on postoperative days 7, 14, and 17 for histological and molecular analysis. Our results showed that DB/+ EPCs were biologically more active than those of DB/DB EPCs. When compared with the control group, local transplantation of EPCs accelerated wound healing in DB/DB mice by promoting wound granulation tissue formation, angiogenesis, and collagen fiber deposition, but there was no significant difference in wound healing between DB/+ EPCs and DB/DB EPCs transplanted into the wound. Furthermore, local transplantation of EPCs promoted the expression of SDF-1, CXCR4, and VEGF. We speculated that EPC transplantation may promote wound healing through the SDF-1/CXCR4 axis. This point is worth exploring further. Present data are of considerable significance because they raise the possibility of promoting wound healing by isolating autologous EPCs from the patient, which provides a new approach for the clinical treatment of diabetic wounds in the future.